Nonlinear pathological trajectory of a high-myopia C57/BL6J mouse model induced by form deprivation - Wen, Yue; Li, Yan; Zhu, Li; Tang, Tao; Yan, Huichao; Hu, Jie; Wang, Kai; Zhao, Mingwei; Xu, Qiong (Frontiers in Physiology, 2024)
IntroductionTo establish a high myopia model in C57BL/6J mice with monocular form deprivation myopia (FDM) and investigate its ocular structure pathological trajectory.MethodsHealthy 3-week-old C57BL/6J mice were divided into an FDM group (n = 36) and a control group (n = 24). The left eyes of the FDM group were patched, while the right eyes served as controls. Biometric parameters and fundus morphology were assessed at baseline and after 4, 8, and 12 weeks of form deprivation.ResultsSignificant differences were observed in the deprived eyes, including longer axial length, higher refractive power, deeper vitreous chambers, thinner retina, choroid, and sclera, and smaller scleral fibers’ diameters under a transmission electron microscope. Retinal vascular area proportion in covered eyes decreased significantly (P < 0.05), with a decline rate of 11% from weeks 4 to 8 and a faster decline of 19% from weeks 8 to 12, while this proportion increased significantly in control eyes.DiscussionThis study successfully induced a high myopia model in mice with long-term form deprivation. The axial length grew dramatically in FDM in the first 8 weeks, while the pathological progress of the fundus accelerated from weeks 8 to 12.